Beyond Population Size: Human Capital, Industrial Upgrading, and the Drivers of Shanghai's Economic Growth - Zhanglin, Chenyue (Simen Owen Academic Proceedings Series, 2025)
This paper investigates Shanghai’s economic growth trajectory from 2014 to 2023, highlighting the city’s strategic shift from population-driven to talent-driven development. During this period, Shanghai’s resident population remained largely stable at approximately 24 million, yet its GDP nearly doubled, reaching 4.72 trillion yuan in 2023. Using regression analysis, the study finds that higher education enrollment exhibits the strongest correlation with GDP growth (r = 0.93), exceeding the influence of both total population and migrant inflows. This underscores the emergence of a “talent dividend” where the quality of human capital increasingly drives economic expansion, effectively replacing the traditional “demographic dividend” associated with sheer population growth. Beyond human capital, complementary factors-including industrial upgrading, accelerated R&D investment, and targeted policy reforms-have reinforced this transition, facilitating structural transformation and innovation-led growth. The findings imply that megacities can sustain high-quality economic growth even under conditions of population stagnation, provided they strategically cultivate skilled talent and foster innovation ecosystems. Policy recommendations emphasize the importance of attracting and nurturing high-skilled workers, investing in advanced research and development, and improving urban livability to enhance long-term competitiveness and resilience in a rapidly evolving global economy.